1989
DOI: 10.1017/s003118200005873x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of Ascaris lumbricoides and other soil-transmitted helminths in primary school children from Ile-Ife, Nigeria

Abstract: An epidemiological survey of intestinal helminthiases was conducted on 766 primary school children aged 5-16 years from Ile-Ife, Nigeria. On the basis of stool examinations, the prevalence of Ascaris lumbricoides, Trichuris trichiura, hookworm and Strongyloides stercoralis was 88.5, 84.5, 33.1 and 3% respectively. Intensity of infection was measured indirectly by egg counts for each species of helminth and also by counting worms passed after chemotherapy in the case of A. lumbricoides. The influence of host ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 17 publications
8
91
2
Order By: Relevance
“…The result of this study is consistent with that of [28] where they reported of increased prevalence of intestinal helminths infections due to bad defecation practices. Also, this result suggests that the type of latrine system used has a majorimpact on the prevalence of intestinal helminths infections among school children.…”
Section: Discussionsupporting
confidence: 91%
“…The result of this study is consistent with that of [28] where they reported of increased prevalence of intestinal helminths infections due to bad defecation practices. Also, this result suggests that the type of latrine system used has a majorimpact on the prevalence of intestinal helminths infections among school children.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the prevalence of Ascaris in the grasscutters is enough to cause public health concern because of the closeness of the rodents to human habitation. Human ascariasis due to Ascaris lumbricoides is very common in Nigeria, with prevalence rates reaching 85.5% in primary school pupils (Holland et al, 1989). Judging by the relative ease with which A. lumbricoides establishes itself experimentally in pigs, a monogastric animal like man, it is not impossible that Ascaris transmission may be on-going between rodents and man with his livestock in the study area.…”
Section: Gastrointestinal Helminth Parasitesmentioning
confidence: 96%
“…This result has further confirmed that rodents transmit zoonotic parasites to man and animals. Trichuriasis is widespread in Nigeria and has been reported by Okpala (1961) and Holland et al (1989). The parasite causes rectal prolapse, anaemia, finger clubbing and retarded growth in man (Jung and Beaver 1951;Bowie et al, 1978 andGilman et al 1983).…”
Section: Gastrointestinal Helminth Parasitesmentioning
confidence: 99%
“…Okpala (1956), Obiamiwe (1977), Reinthale, et al (1988), Onadeko & Ladipo (1989), Holland et al (1989), Fashuyi (1992), Agi (1995), Adeyeba & Akintobi (2002), Ozumba & Ozumba (2002) all observed higher prevalence of Ascaris infection over hookworm and T. trichiura. However, Udonsi et al (1980) and Suswam et al (1992), reported higher prevalence of hookworm infection over other helminths.…”
Section: Introductionmentioning
confidence: 93%